Kajian Efektifitas Operasional Terminal Madyopuro Malang - Anang Bakhtiar; Harnen Sulistio; Sobri Abusini (Jurnal Rekayasa Sipil, 2014)
Madyopuro terminal is sub-terminal and based on information from relevant official that Madyopuro terminal can be classified in the C-type terminals that serve the transportation route in the town and village (31 KM 1995). The existence of various activity centers, one of which is the Madyopuro  market  located adjacent to the Madyopuro terminal should make the effectiveness of   Madyopuro terminal, but in fact,  it is not   effective.   From this background, it is formulated the problem  about what factors influence the effectiveness operasioanl of  Madyopuro terminal Malang, how is the  relationship model between  effectiveness operational  of Madyopuro-terminal Malang with variable facilities, accessibility, services and terminal security and how is  recommendations  of the performance improvement, to the effectiveness operational  of  terminal  of Madyopuro- Malang.  The study was conducted using IPA analysis to determine the factors that affect the effectiveness operational of the terminal, the model and SWOT analysis to get recomendation that resulted. In the first  stages, we did survey related with  influential variables, namely facilities, accessibility, and security services.   From the study, it is conclude that based on the analysis of  IPA found that the factors that influence the effectiveness of terminal services of  Madyopuro-Malang is the arrival and  the departure path, where the waiting room of passangers / companion, vehicle parking and security control of the user, the driver and related official. Model of the relationship of the study was obtained Ymodel = -0.460 + 0.598 X1 + 0.320 X3.While the Ymodel is effectiveness operational of the terminal  and X1 is variable of facility and X3 are variable of  services. From the results of the analysis show that the effectiveness of the terminal with two related variables, namely facilities and services showed a siqnifikan. This is indicated by the value of R2 from 0.868 shows the effect of the relationship is defined by 86.8%. Recommendations  resulting from this study is facility that  needed  to be increase in  improvement of the terminal operational  is an improvement on arrival and departure paths, providing a passenger waiting / delivery, as well as providing vehicle parking lot.  Keywords: effectiveness, Madyopuro terminal, IPA, SWOT